2007
DOI: 10.1017/s0022215107001144
|View full text |Cite
|
Sign up to set email alerts
|

Changing trends in bacteriology of peritonsillar abscess

Abstract: Empirical antibiotics with Gram-negative cover will be appropriate as adjunctive therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 11 publications
2
19
1
Order By: Relevance
“…Sorensen et al [20] studied [20]. The microbiological findings were similar to those from previous reports on peritonsillar abscess [3,6,8,9]. The antibiotic regimen most commonly prescribed (third-generation cephalosporin plus clindamycin) was active against all cultured microorganisms.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…Sorensen et al [20] studied [20]. The microbiological findings were similar to those from previous reports on peritonsillar abscess [3,6,8,9]. The antibiotic regimen most commonly prescribed (third-generation cephalosporin plus clindamycin) was active against all cultured microorganisms.…”
Section: Discussionsupporting
confidence: 68%
“…Patients usually present with severe throat pain, fever, drooling, foul breath, trismus, neck swelling, and altered voice resonance. Microbiological findings for peritonsillar abscesses include both aerobic and anaerobic components [3,[5][6][7][8]. The aerobic bacterium Streptococcus pyogenes is isolated in nearly a third of cases [1].…”
Section: Introductionmentioning
confidence: 99%
“…However, in the work carried out by Snow et al [15], 72.3 % of patients proved to have monomicrobial infection. Also, Megalamani et al [14] identified monomicrobial growth in 65 % of their aerobic cultures. In our work, monomicrobial growth in PTA cultures predominated as well.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of abscesses are polymicrobial infections, with three bacteria regarded to be key causative pathogens: Streptococcus pyogenes , Fusobacterium necrophorum and Streptococcus milleri group [1, 4, 7, 1013]. Monomicrobial infections, however, have been reported as well [14, 15]. Management protocols are lacking, and treatment methods include needle aspiration, surgical drainage or quinsy tonsillectomy combined with antimicrobial therapy [5, 16, 17].…”
Section: Introductionmentioning
confidence: 99%
“…We think that our relatively low rates of anaerobes cultures may be due to inappropriate sampling (by swabs for example). Considering the high percentage of anaerobes and the fact that recurrent peritonsillar abscess is more common in patients infected with anaerobes we therefore strongly recommend the use of antibiotics effective both against aerobic and anaerobic bacteria in the pediatric population [18].…”
Section: Discussionmentioning
confidence: 99%